An Integrated Study to Extrapolate the Interaction of NMDAR with Potential Ligands for the Treatment of Alzheimer’s Disease Symptoms - Varsini S.R.; Samiksha Shivaji Bhor (International Journal of Biochemistry and Biomolecule Research, 2023)
Objective: Alzheimer’s disease (AD) is the most common neurodegenerative disease affecting the health status of older adults especially those above the age of 60 years. As an outcome, two types of medications have been developed for the treatment of its symptoms which are acetylcholinesterase (AChE) and N-methyl-D-aspartate receptor (NMDAR) antagonist. This paper uses the computational approach to understand the interaction of NMDAR with four major phytocompounds (curcumin, L-epicatechin, ginsenosides, and resveratrol) by molecular docking NMDAR against the ligands. Then their therapeutic analysis and pharmacological characteristics were investigated.Method: In this study, the target protein NMDAR was retrieved from PDB and docked against six phytocompounds via PyRx. The binding affinity of the target protein with each ligand was compared and analyzed. Out of the six phytocompounds the top 4 phytocompounds were selected based on their binding affinity, which had to be lower than six. The top 4 were then studied using ADMET and visualized using BIOVIA Discovery Studio Visualizer. Results: Molecular docking results of the target protein, NMDAR, with the top 4 ligands (curcumin, L-epicatechin, ginsenosides, and resveratrol) showed that these ligands have the best binding affinity with the target protein. Conclusion: By analyzing the results, it can be concluded that the top 4 ligands (curcumin, L-epicatechin, ginsenosides, and resveratrol) can be used for the treatment of AD symptoms. However, ligands in vitro and in vivo studies must be carried out to understand the practical use of these ligands.
Keywords: ADMET; Alzheimer’s disease (AD); L-epicatechin; N-methyl-D-aspartate receptor (NMDAR); curcumin; ginsenosides; molecular docking; resveratrol